Csermanek csókja (Privát Magyarország 12)
After 1956 the Hungarian Communist dictatorship under Party Secretary János Kádár was a "softer" version of the Soviet rule. But its double speak, repression and shameless ideological or political perversion contradicts the everyday life behind the doors of private homes. Kádár's Kiss ironically explores the Kafkaesque Hungarian life and politics juxtaposing the public and the private Hungarian histories. "It is said there is a celestial body in the universe, a single, the Sirius Beta cold and dead star a lusterless, heatless motionless body. Where the atoms tossed about and piled on one another, in disarray, as on a colossal junk-heap, rest perished. This is Sirius Beta, material par excellence. When man becomes materialist, or in other words, begins to believe that the world was and is of matter and he adheres to this material, and clings to it, and to him the material means gravity, environment, desire, religion, then man begins to feel obscurely that he is also a fallen and discarded, degraded and broken being tossed aside and on a junk-heap, stripped from contact with the spiritual forces of nature, detached from the cosmos, aborted through terrible catastrophe, his spiritual concern lost, and so he reverts and sinks." Péter Forgács